The economic role of women in agricultural and rural development: the promotion of income-generating activities - Akello, Grace; Sarr, Fatou (Technical Centre for Agricultural and Rural Cooperation, 2000)
The economic role of women in agricultural and rural development: the promotion of income-generating activities